Harnessing Indigenous Fermentation: Probiotic Lactic Acid Bacteria from West Sumatera’s Dadih - Hillman, Prima Fitria; Titisari, Geliz Luh; Syafrizayanti, Syafrizayanti (Jurnal Riset Kimia, 2025)
The potential of lactic acid bacteria (LAB) isolated from dadih, a traditional fermented buffalo milk from West Sumatra, was explored as functional starter cultures for yogurt production. The use of local LAB is considered essential due to Indonesia’s dependence on imported cultures, which often exhibit inconsistent performance and suboptimal quality. This study selected bacterial isolates based on their ability to grow in highly acidic media and their tolerance to bile salt treatment. Molecular identification was conducted by amplifying the 16S rRNA gene using the PCR method. Specific LAB isolates with high probiotic potential were further characterized based on their tolerance to acid and bile salts. The results showed that several LAB strains from dadih, such as Lactococcus lactis, Weissella paramesenteroides, and Weissella sp., exhibited good probiotic properties. These isolates could effectively ferment milk and produce yogurt with organoleptic qualities comparable to commercial cultures. In addition, Serratia marcescens, known as an opportunistic pathogen, was also detected during the isolation process; some of its strains are known to participate in fermentation processes. These findings support the utilization of local LAB as an alternative to imported cultures, promoting local food production, improving the nutritional value of fermented dairy products, and preserving traditional culinary heritage.